Findings of new adventive plant species in Barnaul (Altai Krai) - T. A. Teryokhina; N. V. Ovcharova; M. M. Silanteva (Проблемы ботаники Южной Сибири и Монголии, 2019)
The article describes the characteristics of new plant species for Barnaul. The conditions of their habitat aredescribed. Their ecological and biological characteristics are given and the reasons for the emergence of new advents areindicated. We consider their distribution in the natural and secondary range. Several adventive plant species that are mostabundant in synanthropic habitats are named.